KAOLINISATION OF GRANITE IN AN URBAN ENVIRONMENT - Schiavon N. (My University, 2007)
Under natural acid and wet conditions, one of the main weathering processes affecting granitic rocks is the kaolinisation of Na, Ca and K-feldspar minerals by H2O + CO2 attack. We here report the occurrence of authigenic kaolinite on the surface of an eighteenth century granitic monument covered with sulphate-rich weathering patinas. We suggest that, in humid mesothermic climates, anthropogenically derived gaseous SO2 from air pollution is responsible for accelerated kaolinisation of feldspars in an urban environment; SO2 from air pollution thus plays a dual role in the weathering of silicate rocks being responsible for the well known sulphation of Ca-bearing materials leading to the formation of sulphate salts such as gypsum as well as the weathering of feldspar minerals to kaolinite. The kaolinisation reaction weakens the granite microfabric leading to enhanced decay of the building stone.
Keywords: GRANITE; URBAN ENVIRONMENT; SULPHUR DIOXIDE; FELDSPAR; KAOLINITE; WEATHERING